What do reading times tell us about the effect of orthographic regularity? Evidence from English and Italian readers - Кьяра Валерия Маринелли; Мариалуиза Мартелли; Эмилиано Пицциканнелла; Пьерлуиджи Дзокколотти (Психология человека в образовании, 2023)
Introduction. We examine the impact of orthographic depth focusing on English and Italian—two languages with quite different orthographies.